Soluci´on num´erica de un modelo de ondas localmente amortiguadas - Mal´asquez Chamba, Luz Victoria (2024)
This work aims to solve a wave equation with locally distributed damping with initial and boundary conditions through the linear finite element method. This method’s discretization of the model leads to a system of first-order ordinary differential equations with time-dependent initial values. It is concluded numerically and graphically that the stability of the approximate solution of the model depends on the damping coefficient and stabilizes with time.